Dosimetric impact of dental metallic crown on intensity‐modulated radiotherapy and volumetric‐modulated arc therapy for head and neck cancer. (8th January 2016) - Kamomae, Takeshi; Itoh, Yoshiyuki; Okudaira, Kuniyasu; Nakaya, Takayoshi; Tomida, Masashi; Miyake, Yoshikazu; Oguchi, Hiroshi; Shiinoki, Takehiro; Kawamura, Mariko; Yamamoto, Noriyuki; Naganawa, Shinji
Abstract : Metal dental restoration materials cause dose enhancement upstream and dose disturbance downstream of the high‐density inhomogeneous regions in which these materials are used. In this study, we evaluated the impact of a dental metallic crown (DMC) on intensity‐modulated radiotherapy (IMRT) and volumetric‐modulated arc therapy (VMAT) for head and neck cancer. Additionally, the possibility of sparing the oral mucosa from dose enhancement using an individual intraoral mouthpiece was evaluated. An experimental oral phantom was designed to verify the dosimetric impact of a DMC. We evaluated the effect on single beam, parallel opposing beam, arc beam, IMRT, and VMAT treatment plans. To evaluate the utility of a 3‐mm‐thick intraoral mouthpiece, the doses across the mouthpiece were measured. For single beam irradiation, the measured doses at the entrance and exit planes of the DMC were 51% higher and 21% lower than the calculated dose by the treatment planning system, respectively. The maximum dose enhancements were 22% and 46% for parallel opposing beams and the 90° arc rotation beam, respectively. For IMRT and VMAT, the measured doses adjacent to the DMC were 12.2 % ± 6.3 % ( mean ± 1.96 SD ) and 12.7 % ± 2.5 % higher than the calculated doses, respectively. With regard to the performance of the intraoral mouthpiece for the IMRT and VMAT cases, the disagreement between measured and calculated doses at the outermost surface of the mouthpieces were − 2.0 %, and 2.0%, respectively. Dose enhancements caused by DMC‐mediated radiation scattering occurred during IMRT and VMAT. Because it is difficult to accurately estimate the dose perturbations, careful consideration is necessary when planning head and neck cancer treatments in patients with DMCs. To spare the oral mucosa from dose enhancement, the use of an individual intraoral mouthpiece should be considered. PACS numbers: 87.55.km, 87.55.N‐, 87.55.Qr